Finasteride promotes worsening of the cardiac deleterious effects of nandrolone decanoate and protects against genotoxic and cytotoxic damage (Brazilian Journal of Pharmaceutical Sciences, 2020)
Metabolism of anabolic androgenic steroids is important for its physiological effects. The aim was to investigate the effects of finasteride (a 5α-reductase inhibitor - 5αR) on cardiac and mutagenic effects promoted by ND. Male Wistar rats were separated into three groups: CONT, received the vehicles of ND and finasteride (Peanut oil+Saline); DECA group, received ND (20 mg.kg.week-1, i.m.), and DECAF received ND and finasteride (100 μg.kg-1, i.p.), for four weeks. After, hypertrophy, cytokines and Angiotensin Converting Enzyme (ACE) activity was determined in heart. Bone marrow was used for micronucleus evaluation. Treatment with ND promotes increase in cardiac hypertrophy, ACE activity and disbalance among pro- and anti-inflammatory cytokines, and combination with finasteride worsened those effects. Association with finasteride ameliorates the toxic effects of ND on bone marrow cells, as was observed by a normalization of the number of micronucleate polychromatic erythrocytes and the mitotic index. Our data demonstrates that deleterious effects promoted by ND are depend, at least in part, of its metabolization. Also, inhibition of 5αR by finasteride present variated effects dependent on organ studied. It can promote increase on cardiac damage and a reduction on mutagenic effects of ND, which demonstrated that dehydronandrolone has diverse role on ND effects.